A catalyst for preparing diethyltoluenediamine and its preparation method and use method
By using composite layered metal oxide catalysts in diethyltolyldiamine synthesis process, and by amorphous carbon growth and loading of RuO2, zinc/aluminum elements, high temperature and high pressure, long reaction time in traditional processes are solved by the technical means of high temperature and high pressure and long reaction time and The high cost problem has achieved a significant improvement in catalyst activity and selectivity.
Patent Information
- Application Number
- CN202411090093.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-08-09
AI Technical Summary
The traditional diethyl toluene diamine synthesis process is subject to harsh reaction conditions at high temperature and high pressure, with long reaction time, high production cost, low catalyst activity and low selectivity.
Using composite layered metal oxides as the basis of the catalyst, a catalyst with high specific surface area and catalytic properties is formed through the growth of amorphous carbon and the loading of RuO2, zinc/aluminum elements, and the catalyst is optimized through the reduction step of sodium borohydride. performance.
It significantly improves the activity and selectivity of the catalyst, reduces the reaction activation energy, improves the catalytic reaction capacity and reaction performance, and has broad application prospects.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a catalyst for preparing diethyltoluenediamine and a preparation method and a use method thereof. Background Art
[0002] Amine chain extenders are divided into two categories: aliphatic amines and aromatic amines. 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA) once dominated the aromatic amine chain extenders. Although the resulting product has good mechanical properties, the latest clinical findings show that 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA) has certain carcinogenicity and is harmful to people's physical and mental health. Some European and American countries have strictly restricted its use. The development of new environmentally friendly aromatic amine chain extenders has gradually become an urgent task for the modern chemical industry.
[0003] Diethyltoluenediamine (DETDA) is a light yellow to amber transparent viscous liquid with a slight ammonia smell. It is slightly soluble in water, soluble in polar organic solvents such as alcohol, ether, and ketone, and has good compatibility with polyether and polyester polyols. Diethyltoluenediamine has low viscosity, uniform dispersion, and high chemical activity. It can be used directly as a chain extender, and the reaction is relatively thorough. Comprehensive investigation has found no harm to human health. It is an ideal substitute for 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA). Diethyltoluenediamine has the advantages of short demoulding time, high initial strength, and hydrolysis resistance and heat resistance of the product. It is mainly used as a curing agent, chain extender, polyurethane raw material, amine catalyst, lubricant, antioxidant for industrial oils and fats, and chemical synthesis intermediates.
[0004] The traditional synthesis method of diethyltoluenediamine is to use toluenediamine (TDA) and ethylene as raw materials, and in the presence of a catalyst, a high temperature and high pressure catalytic alkylation reaction occurs, and then the product is refined. In recent years, the demand for diethyltoluenediamine in polyurea elastomers, polyethylene, and polyurethane products has increased rapidly. In the preparation process, it is becoming increasingly important to select new catalysts, improve the selectivity and yield of diethyltoluenediamine, save energy and reduce consumption, improve the production process, and optimize the reaction conditions.
[0005] Catalysts for synthesizing diethyltoluenediamine mainly include: aluminum powder, aluminum chloride, aluminum alkylate, aluminum zinc alloy-aluminum chloride mixed system, aluminum zinc alloy-aluminum chloride-aluminum alkylate mixed system. Aluminum powder has low catalytic activity; aluminum chloride is easy to coke during the reaction; aluminum alkylates such as triethylaluminum are expensive and highly toxic; despite the continuous improvement of the catalytic system, the process for synthesizing diethyltoluenediamine is still limited by the harsh reaction conditions of high temperature and pressure, long reaction time, and high production cost. Summary of the invention
[0006] The purpose of the present invention is to provide a catalyst for preparing diethyltoluenediamine, a preparation method thereof and a use method thereof, which greatly improve the catalytic activity, significantly improve the selectivity of catalytic production of diethyltoluenediamine, and the synergistic effect of each component greatly improves the catalytic reaction ability of the catalyst, improves the reaction performance of the catalyst, reduces the reaction activation energy, and has broad application prospects.
[0007] The technical solution of the present invention is achieved in this way:
[0008] The present invention provides a method for preparing a catalyst for preparing diethyltoluenediamine, comprising the following steps:
[0009] S1. Preparation of composite layered metal oxide: dissolving magnesium nitrate, copper nitrate and nickel nitrate in water, adding alkali solution, heating for crystallization, filtering, washing, drying and calcining to obtain a composite layered metal oxide;
[0010] S2. Growth of amorphous carbon: The composite layered metal oxide is evenly spread out and placed in the center of a quartz porcelain boat, which is placed in a heat preservation zone of a tubular furnace, and heated to a first temperature under the protection of an inert gas, and hydrogen is introduced, and the temperature is raised to a second temperature, and then n-hexane is introduced, and the reaction is kept warm, and then cooled to room temperature under the protection of an inert gas to obtain an amorphous carbon / composite layered metal oxide;
[0011] S3. Loading RuO2: adding amorphous carbon / composite layered metal oxide to water, adding ruthenium chloride, ultrasonically treating, dropping hydrogen peroxide, heating to reflux, filtering, washing, and drying to obtain loaded RuO2 / amorphous carbon / composite layered metal oxide;
[0012] S4. Loading zinc / aluminum elements: Adding RuO2 / amorphous carbon / composite layered metal oxide to water, adding zinc salt and aluminum salt, stirring and mixing at room temperature, impregnating to obtain a mixture;
[0013] S5. Reduction: adding sodium borohydride solution dropwise to the mixture, stirring to react, filtering, washing, and drying to obtain a catalyst for preparing diethyltoluenediamine.
[0014] As a further improvement of the present invention, the mass ratio of magnesium nitrate, copper nitrate and nickel nitrate in step S1 is 3-5:2-4:1-2, the pH value of the solution is adjusted to 7.5-8.5 by dropping alkali solution, the heating crystallization temperature is 85-95°C, the time is 20-40min, and the calcination temperature is 600-700°C, and the time is 2-4h.
[0015] As a further improvement of the present invention, the ventilation rate of n-hexane in step S2 is 0.2-0.4 mL / min, the insulation reaction time is 20-40 min, the first temperature is 420-450° C., and the second temperature is 650-670° C.
[0016] As a further improvement of the present invention, the mass ratio of the amorphous carbon / composite layered metal oxide, ruthenium chloride, and hydrogen peroxide in step S3 is 100:2-4:3-5, the concentration of the hydrogen peroxide is 25-28wt%, the heating reflux reaction time is 2-3h, the power of the ultrasonic treatment is 1000-1200W, and the time is 10-20min.
[0017] As a further improvement of the present invention, the mass ratio of the loaded RuO2 / amorphous carbon / composite layered metal oxide, zinc salt and aluminum salt in step S4 is 10:3-5:5-7, the zinc salt is zinc chloride or zinc nitrate, the aluminum salt is aluminum nitrate, and the impregnation time is 10-12h.
[0018] As a further improvement of the present invention, the concentration of the sodium borohydride solution in step S5 is 0.1-0.15 mol / L, the volume of the sodium borohydride solution is 1 / 7 to 1 / 10 of the mixture, and the stirring reaction time is 1-2 h.
[0019] As a further improvement of the present invention, the present invention specifically comprises the following steps:
[0020] S1. Preparation of composite layered metal oxide: 3-5 parts by weight of magnesium nitrate, 2-4 parts by weight of copper nitrate, and 1-2 parts by weight of nickel nitrate are dissolved in water, and an alkali solution is added dropwise to adjust the pH value to 7.5-8.5, heated to 85-95°C, crystallized for 20-40 minutes, filtered, washed, dried, and calcined at 600-700°C for 2-4 hours to obtain a composite layered metal oxide;
[0021] S2. Growth of amorphous carbon: The composite layered metal oxide is evenly spread out and placed in the center of a quartz porcelain boat, which is then placed in a tube furnace insulation zone. The temperature is raised to 420-450°C under inert gas protection, and hydrogen is introduced, the temperature is raised to 650-670°C, and then n-hexane is introduced at a flow rate of 0.2-0.4 mL / min. The reaction is kept warm for 20-40 minutes, and then cooled to room temperature under inert gas protection to obtain amorphous carbon / composite layered metal oxide;
[0022] S3. Loading RuO2: 100 parts by weight of amorphous carbon / composite layered metal oxide was added to water, 2-4 parts by weight of ruthenium chloride was added, 1000-1200W was ultrasonically treated for 10-20min, 3-5 parts by weight of hydrogen peroxide was added dropwise, the reaction was heated under reflux for 2-3h, filtered, washed, and dried to obtain a loaded RuO2 / amorphous carbon / composite layered metal oxide;
[0023] S4 loaded zinc / aluminum element: 10 parts by weight of loaded RuO2 / amorphous carbon / composite layered metal oxide was added to water, 3-5 parts by weight of zinc salt and 5-7 parts by weight of aluminum salt were added, stirred at room temperature to mix, immersed for 10-12h to obtain a mixture;
[0024] S5. Reduction: add dropwise 0.1-0.15 mol / L sodium borohydride solution to the mixture, wherein the volume of the sodium borohydride solution is 1 / 7 to 1 / 10 of the mixture, stir to react for 1-2 hours, filter, wash, and dry to obtain a catalyst for preparing diethyltoluenediamine.
[0025] The present invention further protects a catalyst for preparing diethyltoluenediamine obtained by the above preparation method.
[0026] The present invention further protects a method for using the catalyst for preparing diethyltoluenediamine. Under the protection of an inert gas, toluenediamine and the catalyst are uniformly mixed, the temperature is increased, ethylene is introduced, the mixture is heated and pressurized for reaction, and the product is vacuum distilled to obtain diethyltoluenediamine.
[0027] As a further improvement of the present invention, the added amount of the catalyst is 0.05-0.1wt% of toluenediamine.
[0028] The present invention has the following beneficial effects:
[0029] The invention prepares a catalyst for preparing diethyltoluenediamine, wherein MgCuNi-LDH is prepared by a coprecipitation method, and then calcined to obtain a composite layered metal oxide, and amorphous carbon is grown on the surface by in-situ catalytic chemical vapor deposition. The prepared amorphous carbon / composite layered metal oxide has a large specific surface area and good catalytic performance.
[0030] By loading ruthenium oxide with excellent catalytic performance on the surface, the diffusion effect of reactant and product molecules in the micropores can be eliminated. At the same time, after further loading zinc / aluminum ions, an aluminum-zinc alloy is formed on the catalyst surface under the reduction action of potassium borohydride, which can prevent the agglomeration of the catalyst during the preparation of amorphous aluminum-zinc, make the aluminum-zinc active centers more dispersed and the electron-rich ability of aluminum-zinc is enhanced, reflecting higher catalytic performance.
[0031] The catalyst prepared by the invention greatly improves the catalytic activity, significantly improves the selectivity for catalytic production of diethyltoluenediamine, and the synergistic effect of each component greatly improves the catalytic reaction ability of the catalyst, improves the reaction performance of the catalyst, reduces the reaction activation energy, and has broad application prospects. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0033] The present embodiment provides a method for preparing a catalyst for preparing diethyltoluenediamine, which specifically comprises the following steps:
[0034] S1. Preparation of composite layered metal oxide: 3 g of magnesium nitrate, 2 g of copper nitrate, and 1 g of nickel nitrate were dissolved in 500 mL of water, and a NaOH solution was added dropwise to adjust the pH value to 7.5, heated to 85°C, crystallized for 20 min, filtered, washed, dried, and calcined at 600°C for 2 h to obtain a composite layered metal oxide;
[0035] S2. Growth of amorphous carbon: The composite layered metal oxide was evenly spread out and placed in the center of a quartz porcelain boat, which was then placed in the insulation zone of a tubular furnace. The temperature was raised to 420°C under nitrogen protection, and then hydrogen was introduced, the temperature was raised to 650°C, and then n-hexane was introduced at a flow rate of 0.2 mL / min. The reaction was kept warm for 20 minutes, and then cooled to room temperature under nitrogen protection to obtain an amorphous carbon / composite layered metal oxide.
[0036] S3. Loading RuO2: 100 g of amorphous carbon / composite layered metal oxide was added to 500 mL of water, 2 g of ruthenium chloride was added, 1000 W ultrasonic treatment was performed for 10 min, 3 g of hydrogen peroxide was added dropwise, the reaction was heated under reflux for 2 h, filtered, washed, and dried to obtain loaded RuO2 / amorphous carbon / composite layered metal oxide;
[0037] S4. Loading zinc / aluminum elements: 10g of loaded RuO2 / amorphous carbon / composite layered metal oxide was added to 500mL of water, 3g of zinc chloride and 5g of aluminum nitrate were added, stirred and mixed at room temperature, and immersed for 10h to obtain a mixture;
[0038] S5. Reduction: add dropwise 0.1 mol / L sodium borohydride solution to the mixture, wherein the volume of the sodium borohydride solution is 1 / 7 of the mixture, stir and react for 1 hour, filter, wash and dry to obtain a catalyst for preparing diethyltoluenediamine. Example 2
[0039] The present embodiment provides a method for preparing a catalyst for preparing diethyltoluenediamine, which specifically comprises the following steps:
[0040] S1. Preparation of composite layered metal oxide: 5 g of magnesium nitrate, 4 g of copper nitrate, and 2 g of nickel nitrate were dissolved in 500 mL of water, and a NaOH solution was added dropwise to adjust the pH value to 8.5, heated to 95°C, crystallized for 40 min, filtered, washed, dried, and calcined at 700°C for 4 h to obtain a composite layered metal oxide;
[0041] S2. Growth of amorphous carbon: The composite layered metal oxide was evenly spread out and placed in the center of a quartz porcelain boat, which was then placed in the insulation zone of a tubular furnace. The temperature was raised to 450°C under nitrogen protection, and then hydrogen was introduced, the temperature was raised to 670°C, and then n-hexane was introduced at a flow rate of 0.4 mL / min. The reaction was kept warm for 40 minutes, and then cooled to room temperature under nitrogen protection to obtain an amorphous carbon / composite layered metal oxide.
[0042] S3. Loading RuO2: 100 g of amorphous carbon / composite layered metal oxide was added to 500 mL of water, 4 g of ruthenium chloride was added, ultrasonic treatment was performed at 1200 W for 20 min, 5 g of hydrogen peroxide was added dropwise, the reaction was heated under reflux for 3 h, filtered, washed, and dried to obtain loaded RuO2 / amorphous carbon / composite layered metal oxide;
[0043] S4. Loading zinc / aluminum elements: 10 g of loaded RuO2 / amorphous carbon / composite layered metal oxide was added to 500 mL of water, 5 g of zinc nitrate and 7 g of aluminum nitrate were added, stirred and mixed at room temperature, and immersed for 12 h to obtain a mixture;
[0044] S5. Reduction: add dropwise 0.15 mol / L sodium borohydride solution to the mixture, wherein the volume of the sodium borohydride solution is 1 / 7 to 1 / 10 of the mixture, stir and react for 2 h, filter, wash and dry to obtain a catalyst for preparing diethyltoluenediamine. Example 3
[0045] The present embodiment provides a method for preparing a catalyst for preparing diethyltoluenediamine, which specifically comprises the following steps:
[0046] S1. Preparation of composite layered metal oxide: 4 g of magnesium nitrate, 3 g of copper nitrate, and 1.5 g of nickel nitrate were dissolved in 500 mL of water, and a NaOH solution was added dropwise to adjust the pH value to 8, heated to 90°C, crystallized for 30 min, filtered, washed, dried, and calcined at 650°C for 3 h to obtain a composite layered metal oxide;
[0047] S2. Growth of amorphous carbon: The composite layered metal oxide was evenly spread out and placed in the center of a quartz porcelain boat, which was then placed in a tubular furnace insulation zone. The temperature was raised to 435°C under nitrogen protection, and hydrogen was introduced, and the temperature was raised to 660°C. Then n-hexane was introduced at a flow rate of 0.3 mL / min, and the reaction was kept warm for 30 minutes. The mixture was then cooled to room temperature under nitrogen protection to obtain an amorphous carbon / composite layered metal oxide.
[0048] S3. Loading RuO2: 100 g of amorphous carbon / composite layered metal oxide was added to 500 mL of water, 3 g of ruthenium chloride was added, ultrasonic treatment was performed at 1100 W for 15 min, 4 g of hydrogen peroxide was added dropwise, the reaction was heated under reflux for 2.5 h, filtered, washed, and dried to obtain loaded RuO2 / amorphous carbon / composite layered metal oxide;
[0049] S4. Loading zinc / aluminum elements: 10 g of loaded RuO2 / amorphous carbon / composite layered metal oxide was added to 500 mL of water, 4 g of zinc chloride and 6 g of aluminum nitrate were added, stirred and mixed at room temperature, and immersed for 11 h to obtain a mixture;
[0050] S5. Reduction: add dropwise 0.12 mol / L sodium borohydride solution to the mixture, wherein the volume of the sodium borohydride solution is 1 / 8 of the mixture, stir and react for 1.5 h, filter, wash and dry to obtain a catalyst for preparing diethyltoluenediamine.
[0051] Comparative Example 1
[0052] Compared with Example 3, the difference is that copper nitrate and nickel nitrate are not added in step S1.
[0053] The details are as follows:
[0054] S1. Preparation of layered metal oxide: 8.5 g of magnesium nitrate was dissolved in 500 mL of water, and NaOH solution was added dropwise to adjust the pH value to 8, heated to 90°C, crystallized for 30 min, filtered, washed, dried, and calcined at 650°C for 3 h to obtain a layered metal oxide;
[0055] S2. Growth of amorphous carbon: evenly spread the layered metal oxide and place it in the center of a quartz porcelain boat, place it in the insulation zone of a tubular furnace, heat it to 435°C under nitrogen protection, change to hydrogen, heat it to 660°C, then introduce n-hexane at a flow rate of 0.3 mL / min, keep the temperature for 30 minutes, then cool it to room temperature under nitrogen protection to obtain amorphous carbon / layered metal oxide;
[0056] S3. Loading RuO2: 100 g of amorphous carbon / layered metal oxide was added to 500 mL of water, 3 g of ruthenium chloride was added, ultrasonic treatment was performed at 1100 W for 15 min, 4 g of hydrogen peroxide was added dropwise, the reaction was heated under reflux for 2.5 h, filtered, washed, and dried to obtain loaded RuO2 / amorphous carbon / layered metal oxide;
[0057] S4. Loading zinc / aluminum elements: 10 g of loaded RuO2 / amorphous carbon / layered metal oxide was added to 500 mL of water, 4 g of zinc chloride and 6 g of aluminum nitrate were added, stirred and mixed at room temperature, and immersed for 11 h to obtain a mixture;
[0058] S5. Reduction: add dropwise 0.12 mol / L sodium borohydride solution to the mixture, wherein the volume of the sodium borohydride solution is 1 / 8 of the mixture, stir and react for 1.5 h, filter, wash and dry to obtain a catalyst for preparing diethyltoluenediamine.
[0059] Comparative Example 2
[0060] Compared with Example 3, the difference is that step S2 is not performed.
[0061] Specific person:
[0062] S1. Preparation of composite layered metal oxide: 4 g of magnesium nitrate, 3 g of copper nitrate, and 1.5 g of nickel nitrate were dissolved in 500 mL of water, and a NaOH solution was added dropwise to adjust the pH value to 8, heated to 90°C, crystallized for 30 min, filtered, washed, dried, and calcined at 650°C for 3 h to obtain a composite layered metal oxide;
[0063] S2. Loading RuO2: 100 g of the composite layered metal oxide was added to 500 mL of water, 3 g of ruthenium chloride was added, ultrasonic treatment was performed at 1100 W for 15 min, 4 g of hydrogen peroxide was added dropwise, the reaction was heated under reflux for 2.5 h, filtered, washed, and dried to obtain a loaded RuO2 / composite layered metal oxide;
[0064] S3 loaded zinc / aluminum element: 10g loaded RuO2 / composite layered metal oxide was added to 500mL of water, 4g of zinc chloride and 6g of aluminum nitrate were added, stirred at room temperature and mixed, immersed for 11h to obtain a mixture;
[0065] S4. Reduction: add dropwise 0.12 mol / L sodium borohydride solution to the mixture, wherein the volume of the sodium borohydride solution is 1 / 8 of the mixture, stir and react for 1.5 h, filter, wash and dry to obtain a catalyst for preparing diethyltoluenediamine.
[0066] Comparative Example 3
[0067] Compared with Example 3, the difference is that step S3 is not performed.
[0068] The details are as follows:
[0069] S1. Preparation of composite layered metal oxide: 4 g of magnesium nitrate, 3 g of copper nitrate, and 1.5 g of nickel nitrate were dissolved in 500 mL of water, and a NaOH solution was added dropwise to adjust the pH value to 8, heated to 90°C, crystallized for 30 min, filtered, washed, dried, and calcined at 650°C for 3 h to obtain a composite layered metal oxide;
[0070] S2. Growth of amorphous carbon: The composite layered metal oxide was evenly spread out and placed in the center of a quartz porcelain boat, which was then placed in a tubular furnace insulation zone. The temperature was raised to 435°C under nitrogen protection, and hydrogen was introduced, and the temperature was raised to 660°C. Then n-hexane was introduced at a flow rate of 0.3 mL / min, and the reaction was kept warm for 30 minutes. The mixture was then cooled to room temperature under nitrogen protection to obtain an amorphous carbon / composite layered metal oxide.
[0071] S3. Loading zinc / aluminum elements: 10g of amorphous carbon / composite layered metal oxide was added to 500mL of water, 4g of zinc chloride and 6g of aluminum nitrate were added, stirred and mixed at room temperature, and immersed for 11h to obtain a mixture;
[0072] S4. Reduction: add dropwise 0.12 mol / L sodium borohydride solution to the mixture, wherein the volume of the sodium borohydride solution is 1 / 8 of the mixture, stir and react for 1.5 h, filter, wash and dry to obtain a catalyst for preparing diethyltoluenediamine.
[0073] Comparative Example 4
[0074] Compared with Example 3, the difference is that zinc chloride is not added in step S4.
[0075] The details are as follows:
[0076] S1. Preparation of composite layered metal oxide: 4 g of magnesium nitrate, 3 g of copper nitrate, and 1.5 g of nickel nitrate were dissolved in 500 mL of water, and a NaOH solution was added dropwise to adjust the pH value to 8, heated to 90°C, crystallized for 30 min, filtered, washed, dried, and calcined at 650°C for 3 h to obtain a composite layered metal oxide;
[0077] S2. Growth of amorphous carbon: The composite layered metal oxide was evenly spread out and placed in the center of a quartz porcelain boat, which was then placed in a tubular furnace insulation zone. The temperature was raised to 435°C under nitrogen protection, and hydrogen was introduced, and the temperature was raised to 660°C. Then n-hexane was introduced at a flow rate of 0.3 mL / min, and the reaction was kept warm for 30 minutes. The mixture was then cooled to room temperature under nitrogen protection to obtain an amorphous carbon / composite layered metal oxide.
[0078] S3. Loading RuO2: 100 g of amorphous carbon / composite layered metal oxide was added to 500 mL of water, 3 g of ruthenium chloride was added, ultrasonic treatment was performed at 1100 W for 15 min, 4 g of hydrogen peroxide was added dropwise, the reaction was heated under reflux for 2.5 h, filtered, washed, and dried to obtain loaded RuO2 / amorphous carbon / composite layered metal oxide;
[0079] S4 loaded aluminum element: 10g loaded RuO2 / amorphous carbon / composite layered metal oxide was added to 500mL of water, 10g of aluminum nitrate was added, stirred and mixed at room temperature, and immersed for 11h to obtain a mixture;
[0080] S5. Reduction: add dropwise 0.12 mol / L sodium borohydride solution to the mixture, wherein the volume of the sodium borohydride solution is 1 / 8 of the mixture, stir and react for 1.5 h, filter, wash and dry to obtain a catalyst for preparing diethyltoluenediamine.
[0081] Comparative Example 5
[0082] Compared with Example 3, the difference is that aluminum nitrate is not added in step S4.
[0083] The details are as follows:
[0084] S1. Preparation of composite layered metal oxide: 4 g of magnesium nitrate, 3 g of copper nitrate, and 1.5 g of nickel nitrate were dissolved in 500 mL of water, and a NaOH solution was added dropwise to adjust the pH value to 8, heated to 90°C, crystallized for 30 min, filtered, washed, dried, and calcined at 650°C for 3 h to obtain a composite layered metal oxide;
[0085] S2. Growth of amorphous carbon: The composite layered metal oxide was evenly spread out and placed in the center of a quartz porcelain boat, which was then placed in a tubular furnace insulation zone. The temperature was raised to 435°C under nitrogen protection, and hydrogen was introduced, and the temperature was raised to 660°C. Then n-hexane was introduced at a flow rate of 0.3 mL / min, and the reaction was kept warm for 30 minutes. The mixture was then cooled to room temperature under nitrogen protection to obtain an amorphous carbon / composite layered metal oxide.
[0086] S3. Loading RuO2: 100 g of amorphous carbon / composite layered metal oxide was added to 500 mL of water, 3 g of ruthenium chloride was added, ultrasonic treatment was performed at 1100 W for 15 min, 4 g of hydrogen peroxide was added dropwise, the reaction was heated under reflux for 2.5 h, filtered, washed, and dried to obtain loaded RuO2 / amorphous carbon / composite layered metal oxide;
[0087] S4 loaded with zinc element: 10g loaded RuO2 / amorphous carbon / composite layered metal oxide was added to 500mL of water, 10g of zinc chloride was added, stirred and mixed at room temperature, and immersed for 11h to obtain a mixture;
[0088] S5. Reduction: add dropwise 0.12 mol / L sodium borohydride solution to the mixture, wherein the volume of the sodium borohydride solution is 1 / 8 of the mixture, stir and react for 1.5 h, filter, wash and dry to obtain a catalyst for preparing diethyltoluenediamine.
[0089] Comparative Example 6
[0090] Compared with Example 3, the difference is that step S4 is not performed.
[0091] The details are as follows:
[0092] S1. Preparation of composite layered metal oxide: 4 g of magnesium nitrate, 3 g of copper nitrate, and 1.5 g of nickel nitrate were dissolved in 500 mL of water, and a NaOH solution was added dropwise to adjust the pH value to 8, heated to 90°C, crystallized for 30 min, filtered, washed, dried, and calcined at 650°C for 3 h to obtain a composite layered metal oxide;
[0093] S2. Growth of amorphous carbon: The composite layered metal oxide was evenly spread out and placed in the center of a quartz porcelain boat, which was then placed in a tubular furnace insulation zone. The temperature was raised to 435°C under nitrogen protection, and hydrogen was introduced, and the temperature was raised to 660°C. Then n-hexane was introduced at a flow rate of 0.3 mL / min, and the reaction was kept warm for 30 minutes. The mixture was then cooled to room temperature under nitrogen protection to obtain an amorphous carbon / composite layered metal oxide.
[0094] S3. Loading RuO2: 100 g of amorphous carbon / composite layered metal oxide was added to 500 mL of water, 3 g of ruthenium chloride was added, ultrasonic treatment was performed at 1100 W for 15 min, 4 g of hydrogen peroxide was added dropwise, the reaction was heated under reflux for 2.5 h, filtered, washed, and dried to obtain loaded RuO2 / amorphous carbon / composite layered metal oxide;
[0095] S4. Reduction: Add 10 g of loaded RuO2 / amorphous carbon / composite layered metal oxide into 500 mL of water to obtain a mixture, add dropwise 0.12 mol / L sodium borohydride solution, the volume of which is 1 / 8 of the mixture, stir the reaction for 1.5 h, filter, wash, and dry to obtain a catalyst for preparing diethyltoluenediamine.
[0096] Comparative Example 7
[0097] Compared with Embodiment 3, the difference is that step S5 is not performed.
[0098] The details are as follows:
[0099] S1. Preparation of composite layered metal oxide: 4 g of magnesium nitrate, 3 g of copper nitrate, and 1.5 g of nickel nitrate were dissolved in 500 mL of water, and a NaOH solution was added dropwise to adjust the pH value to 8, heated to 90°C, crystallized for 30 min, filtered, washed, dried, and calcined at 650°C for 3 h to obtain a composite layered metal oxide;
[0100] S2. Growth of amorphous carbon: The composite layered metal oxide was evenly spread out and placed in the center of a quartz porcelain boat, which was then placed in a tubular furnace insulation zone. The temperature was raised to 435°C under nitrogen protection, and hydrogen was introduced, and the temperature was raised to 660°C. Then n-hexane was introduced at a flow rate of 0.3 mL / min, and the reaction was kept warm for 30 minutes. The mixture was then cooled to room temperature under nitrogen protection to obtain an amorphous carbon / composite layered metal oxide.
[0101] S3. Loading RuO2: 100 g of amorphous carbon / composite layered metal oxide was added to 500 mL of water, 3 g of ruthenium chloride was added, ultrasonic treatment was performed at 1100 W for 15 min, 4 g of hydrogen peroxide was added dropwise, the reaction was heated under reflux for 2.5 h, filtered, washed, and dried to obtain loaded RuO2 / amorphous carbon / composite layered metal oxide;
[0102] S4. Loading zinc / aluminum elements: Add 10 g of loaded RuO2 / amorphous carbon / composite layered metal oxide into 500 mL of water, add 4 g of zinc chloride and 6 g of aluminum nitrate, stir and mix evenly at room temperature, soak for 11 h, filter, wash, and dry to obtain a catalyst for preparing diethyltoluenediamine.
[0103] Test Example 1
[0104] The specific surface area and total pore volume of the catalysts for preparing diethyltoluenediamine prepared in Examples 1-3 and Comparative Examples 1-7 were measured using a 3-FLEX 3500 multi-station high-throughput gas adsorption instrument.
[0105] The results are shown in Table 1.
[0106] Table 1 ;
[0107] It can be seen from the above table that the catalysts for preparing diethyltoluenediamine prepared in Examples 1-3 of the present invention have larger specific surface areas and total pore volumes.
[0108] Test Example 2
[0109] Under nitrogen protection, toluenediamine and the catalyst for preparing diethyltoluenediamine prepared in Example 1-3 or Comparative Example 1-7 were uniformly mixed, the added amount of the catalyst was 0.05wt% of toluenediamine, the temperature was raised to 95°C, ethylene was introduced, heated to 195°C, pressurized to 1.1MPa, reacted for 1h, and the product was distilled in two stages. First, the light component was distilled at a vacuum degree of 0.92MPa and a temperature of 155°C, and removed; then the pressure was maintained and the temperature was raised to 175°C, and the distilled components were collected, which were diethyltoluenediamine.
[0110] The results of toluenediamine conversion rate, diethyltoluenediamine product purity and reaction selectivity in the catalytic reaction of each group of catalysts were recorded.
[0111] The results are shown in Table 2.
[0112] Table 2 ;
[0113] It can be seen from the above table that in the catalytic reaction of the catalyst for preparing diethyltoluenediamine prepared in Examples 1-3 of the present invention, the toluenediamine conversion rate is high, the reaction selectivity is good, and the diethyltoluenediamine has a high purity.
[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a catalyst for preparing diethyltoluenediamine, characterized in that: The following steps are involved: S1. Preparation of composite layered metal oxide: dissolving magnesium nitrate, copper nitrate and nickel nitrate in water, dropping alkali solution, heating for crystallization, filtering, washing, drying and calcining to obtain composite layered metal oxide; the mass ratio of magnesium nitrate, copper nitrate and nickel nitrate is 3-5:2-4:1-2; the pH value of the solution is adjusted to 7.5-8.5 by dropping alkali solution, the temperature of heating for crystallization is 85-95°C, the time is 20-40min, the temperature of calcining is 600-700°C, and the time is 2-4h; S2. Growth of amorphous carbon: The composite layered metal oxide is evenly spread out and placed in the center of a quartz porcelain boat, which is then placed in a tube furnace insulation zone, and heated to 420-450°C under inert gas protection, and then hydrogen is introduced, and the temperature is raised to 650-670°C, and then n-hexane is introduced, and the reaction is kept warm, and then cooled to room temperature under inert gas protection to obtain amorphous carbon / composite layered metal oxide; S3. Loading RuO2: adding amorphous carbon / composite layered metal oxide to water, adding ruthenium chloride, ultrasonically treating, dropping hydrogen peroxide, heating to reflux reaction, filtering, washing, and drying to obtain loaded RuO2 / amorphous carbon / composite layered metal oxide; the mass ratio of the amorphous carbon / composite layered metal oxide, ruthenium chloride, and hydrogen peroxide is 100:2-4:3-5; S4. Loading zinc / aluminum elements: adding the loaded RuO2 / amorphous carbon / composite layered metal oxide to water, adding zinc salt and aluminum salt, stirring and mixing at room temperature, and impregnating to obtain a mixture; the mass ratio of the loaded RuO2 / amorphous carbon / composite layered metal oxide, zinc salt and aluminum salt is 10:3-5:5-7, the zinc salt is zinc chloride or zinc nitrate, and the aluminum salt is aluminum nitrate; S5. Reduction: adding sodium borohydride solution dropwise to the mixture, stirring to react, filtering, washing, and drying to obtain a catalyst for preparing diethyltoluenediamine.
2. The preparation method according to claim 1, characterized in that: The ventilation rate of n-hexane in step S2 is 0.2-0.4 mL / min, and the insulation reaction time is 20-40 min.
3. The preparation method according to claim 1, characterized in that: The concentration of the hydrogen peroxide in step S3 is 25-28wt%, the heating reflux reaction time is 2-3h, the power of the ultrasonic treatment is 1000-1200W, and the time is 10-20min.
4. The preparation method according to claim 1, characterized in that: The immersion time in step S4 is 10-12 hours.
5. The preparation method according to claim 1, characterized in that: In step S5, the concentration of the sodium borohydride solution is 0.1-0.15 mol / L, the volume of the sodium borohydride solution is 1 / 7 to 1 / 10 of the mixture, and the stirring reaction time is 1-2 h.
6. A catalyst for preparing diethyltoluenediamine obtained by the preparation method according to any one of claims 1 to 5.
7. A method for using the catalyst for preparing diethyltoluenediamine as claimed in claim 6, characterized in that: Under the protection of inert gas, toluenediamine and catalyst are mixed evenly, the temperature is raised, ethylene is introduced, the reaction is heated and pressurized, and the product is vacuum distilled to obtain diethyltoluenediamine.
8. The method of use according to claim 7, characterized in that: The added amount of the catalyst is 0.05-0.1 wt % of toluenediamine.
Citation Information
Patent Citations
Method for synthesizing diethyltoluenediamine
CN106083605A
Synthesis method of diethyltoluenediamine
CN106946714A